Economic systems : a comparative analysis - Halm, George N. (New York : Holt, Rinehart and Winston, 1960)
The book is written as a text for the course in Comparative Economic System which is now offered at many American colleges. Emphasis is placed on theoretical analysis rather than on a description of the economies of various countries.
Includes bibliographical footnotes and index.
rpm 05/07/2017
Loans
Keywords: Comparative economics